Pangenome-wide analysis of cyclic nucleotide-gated channel (CNGC) gene family in citrus Spp. Revealed their intraspecies diversity and potential roles in abiotic stress tolerance - Zia, Komal; Rao, Muhammad Junaid; Sadaqat, Muhammad; Azeem, Farrukh; Fatima, Kinza; Tahir ul Qamar, Muhammad; Alshammari, Abdulrahman; Alharbi, Metab (Frontiers in Genetics, 2022)
Cyclic nucleotide-gated channels (CNGC) gene family has been found to be involved in physiological processes including signaling pathways, environmental stresses, plant growth, and development. The pangenome-wide study overcomes the limitations associated with single reference genome-based analysis and enable us to understand the diversity of gene family members comprehensively. In the current study pangenome-wide analysis of the CNGC gene family has been done in five Citrus species. As a result, a total of 32 genes in C. sinensis, 27 genes in C. recticulata, 30 genes in C. grandis, 31 genes in A. buxfolia, and 30 genes in P. trifoliata were identified. In addition, two unique genes CNGC13 and CNGC14 were also identified, which may have potential roles in these plant species. All the identified CNGC genes were unevenly distributed on Citrus Spp. chromosomes and were classified into four major groups and two sub-groups. Cyclic nucleotide binding motif, calmodulin-binding motif, and motif for IQ-domain were conserved in Citrus Spp. Intron exon structures of citrus species were not exactly as same as the gene structures of Arabidopsis. The majority of cis-regulatory elements were light responsive and others include growth, development, and stress-related. Both segmental and tandem duplication were involved in the expansion of the CNGC gene family. The miRNAs are involved in the response of CsCNGC genes towards drought stress along with having regulatory association in the expression of these genes. Protein- Protein interaction (PPI) analysis also showed the interaction of CNGC proteins with other CNGCs and other proteins suggesting a potential role pathways regulating different biological processes. GO enrichment revealed that CNGC genes were involved in the transport of ions across membranes. Furthermore, tissue-specific expression patterns of leaves sample of C. sinensis were studied under drought stress. Out of 32 genes of C. sinensis 3 genes i.e., CsCNGC1.4, CsCNGC2.1, and CsCNGC4.2 were highly up-regulated, and only CsCNGC4.6 was highly down-regulated. This work includes findings based on multiple genomes instead of one, therefore, this will help provide more genomic information rather than single genome-based studies.